Virtue, emotion, and imagination in law and legal reasoning - Amaya, Amalia; Del Mar, Maksymilian, 1979- (Chicago : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"What is the role and value of virtue, emotion and imagination in law and legal reasoning? These new essays, by leading scholars of both law and philosophy, offer striking and exploratory answers to this neglected question. The collection takes a holistic approach, inquiring as to the connections and relations between virtue, emotion and imagination. In addition to the principal focus on adjudication, essays in the collection also engage with a variety of different legal, political and moral contexts: eg criminal law sentencing, the Black Lives Matter movement and professional ethics. A number of different areas of the law are addressed (eg criminal law, constitutional law and tort law) and the issues explored include: the benefits and limits of empathy in legal reasoning; the role of attention and perception in judicial reasoning;, the identification of judicial virtues (such as compassion and humility) and judicial vices (such as callousness and partiality); the values and dangers of certain imaginative devices (eg personification); and the interactive and social dimensions of virtue, emotion and imagination"--
1. New Horizons for the Study of the Legal Mind: Relating Virtue, Emotion and Imagination Amalia Amaya and Maksymilian Del Mar -- PART I VIRTUE - AND EMOTION, IMAGINATION 2. Admiration, Exemplarity and Judicial Virtue Amalia Amaya 3. Impartiality and Legal Reasoning Catherine Z Elgin 4. Austerity, Compassion and the Rule of Law Benjamin C Zipursky 5. All Judges on the Couch? On Iris Murdoch and Legal Decision-Making Iris van Domselaar -- PART II EMOTION - AND VIRTUE, IMAGINATION 6. On Emotions and the Politics of Attention in Judicial Reasoning Emily Kidd White 7. 'Black Lives Matter': Moral Frames for Understanding the Police Killings of Black Males Lawrence Blum 8. Suffering and Punishment Michael S Brady 9. Empathy and Negative Intimacy Olbeth Hansberg -- PART III IMAGINATION - AND EMOTION, VIRTUE 10. Empathy, Imagination and the Law Amy Kind 11. Imagining Motives Adam Morton 12. The Legal Imagination in Historical Perspective Simon Stern 13. The Legal Imagination: Individual, Interactive and Communal Maksymilian Del Mar.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law -- Methodology; Law -- Philosophy; Virtue; Emotions (Philosophy); Imagination; Jurisprudence & philosophy of law; Electronic books